2017
DOI: 10.1002/2016jd026401
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous ice nucleation of α‐pinene SOA particles before and after ice cloud processing

Abstract: The ice nucleation ability of α‐pinene secondary organic aerosol (SOA) particles was investigated at temperatures between 253 and 205 K in the Aerosol Interaction and Dynamics in the Atmosphere cloud simulation chamber. Pristine SOA particles were nucleated and grown from pure gas precursors and then subjected to repeated expansion cooling cycles to compare their intrinsic ice nucleation ability during the first nucleation event with that observed after ice cloud processing. The unprocessed α‐pinene SOA partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(90 citation statements)
references
References 66 publications
(166 reference statements)
8
82
0
Order By: Relevance
“…Further studies found that SOA from α-pinene is initially an inefficient INP under cirrus cloud conditions and shows an increased ice nucleation ability when precooled or preactivated, i.e. after cloud processing, where the aerosol first activated to supercooled cloud droplets and then froze homogeneously (Ladino et al, 2014;Wagner et al, 2017). These and other studies on the ice-nucleating ability of SOA particles are summarized in Hoose and Möhler (2012) and Knopf et al (2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Further studies found that SOA from α-pinene is initially an inefficient INP under cirrus cloud conditions and shows an increased ice nucleation ability when precooled or preactivated, i.e. after cloud processing, where the aerosol first activated to supercooled cloud droplets and then froze homogeneously (Ladino et al, 2014;Wagner et al, 2017). These and other studies on the ice-nucleating ability of SOA particles are summarized in Hoose and Möhler (2012) and Knopf et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the different particle generation procedures, the resulting particle sizes vary, too, which certainly alters the ice nucleation capability (larger particles provide a larger surface area and are more likely to form ice). The findings of the above-mentioned studies can be summarized as follows: Wang et al (2012) and Ignatius et al (2016) found that atmospheric SOA particles are potentially important for ice nucleation due to their semi-solid or solid phase states by investigating SOA from naphthalene and α-pinene, respectively, whereas Ladino et al (2014) and Wagner et al (2017) found that α-pinene SOA at first is an inefficient INP at cirrus temperatures, but after precooling of the SOA particles, ice nucleation ability is increased. Schill et al (2014) found that semi-solid or glassy SOA from aqueous processing of methylglyoxal with methylamine is a poor depositional INP; however, Wilson et al (2012) found other aqueous glassy aerosol to nucleate ice heterogeneously at temperatures relevant for cirrus formation in the tropical tropopause layer.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations